2019
DOI: 10.1002/ejic.201801263
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Terpyridine‐Based Coordination for the Construction of Photoactive Supramolecular Structures

Abstract: Exploring new materials to manipulate luminescent radiation and investigate the interaction of light and matter is one of the most compelling prospects of our century. Supramolecular chemistry has unraveled the opportunity to synergistically combine the chemical and optoelectronic properties of the most diverse classes of compounds. Among these, terpyridines have acted as pivotal ligand units that enable selfassembly of multicomponent chromophoric systems. In this review we therefore elucidate the metal-coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
81
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(86 citation statements)
references
References 40 publications
5
81
0
Order By: Relevance
“…In each compound, the cobalt atom acts as a four-connecting node, and adjacent metal centers are bridged by 3,2 :6 ,3"-tpy units to produce (4,4) nets. This is reminiscent of the coordination networks assembled from Co(NCS) 2 and 4,2 :6 ,4"-tpy ligands functionalized with 4 -tert-butyl, 4 -(4-methoxyphenyl), 4 -(4-ethoxyphenyl) and 4 -(4-n-propoxyphenyl) substituents [23].…”
Section: Crystal Structuresmentioning
confidence: 99%
See 3 more Smart Citations
“…In each compound, the cobalt atom acts as a four-connecting node, and adjacent metal centers are bridged by 3,2 :6 ,3"-tpy units to produce (4,4) nets. This is reminiscent of the coordination networks assembled from Co(NCS) 2 and 4,2 :6 ,4"-tpy ligands functionalized with 4 -tert-butyl, 4 -(4-methoxyphenyl), 4 -(4-ethoxyphenyl) and 4 -(4-n-propoxyphenyl) substituents [23].…”
Section: Crystal Structuresmentioning
confidence: 99%
“…In contrast, in [Co 2 (5) 4 (NCS) 4 ] n and [Co(6) 2 (NCS) 2 ] n , the 2D-networks pack in an ABAB... fashion (Figure 8), allowing the n-pentyloxy and n-hexyloxy to penetrate into the cavities in an adjacent sheet. A significant point is that in the case of the reaction of Co(NCS) 2 with ligand 1, there is competition between the formation of a (4,4) [19]) and a 1D-coordination polymer [Co(1)(NCS) 2 (MeOH) 2 ] n , with the 1D-coordination polymer being the dominant product [19]. Powder XRD confirmed that this is not the case for the coordination polymers formed with ligands 5 and 6, and the single-crystal structures of [Co 2 (5) [19].…”
Section: Crystal Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The coordination chemistry of 2,2′:6′,2″-terpyridine (tpy) is well established, and is dominated by tpy acting as a bis-chelating ligand [ 1 , 2 , 3 , 4 , 5 ]. The terpyridine isomers 3,2′:6′,3″-tpy and 4,2′:6′,4″-tpy ( Scheme 1 a) are growing in popularity as building blocks in coordination polymers owing to the vectorial properties of the outer pyridine N -donors, and the fact that the central pyridine ring is coordinatively innocent [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%